Historiography as a Subject of Conceptual and Axiological Analysis (Based on Sources about MICHEL MONTAIGNE) - Rayskina, Valeriya A. (Aktualʹnye problemy filologii i pedagogičeskoj lingvistiki, 2021)
The paper presents the procedure and results of conceptual and axiological analysis based on sources related to life and work of the XVIth century writer, humanist, and philosopher Michel Montaigne. The aim of the conceptual and axiological analysis is to identify notional, ontological, and value-based categories in the prepared historiographical corpus. The analysis was based on Russian, English, French, Italian, German, and Ukrainian texts related to scientific and historical discourse of various themes but united in personality of M. Montaigne. The study appeals to the term personal historiography introduced and used as textual repertory, which forms a well-balances corpus representing the information about a person in the example of M. Montaigne. Several conceptual and axiological components are revealed on the paratextual layer. The linguistic-axiological analysis of titles of texts about M. Montaigne aims to reveal recurrent means used to express verbal subjective evaluations and axiological dominants in modern researchers` discourse dedicated to life, work, and art of the Renaissance philosopher. The overall purpose of the multidisciplinary study of titles, which includes lexical, semantical, conceptual, axiological and content-analysis is to classify concepts, representing central concerns of Montaigne`s researchers, but also to identify axiological dominants of these researches. The analysis resulted in the determination of several basic concept fields perceived as set of concepts` representations with common features. All the recurrent concepts belong to highly various fields: philosophical beliefs; writing; values and anti-values; others; self-identity; intertextuality; politics; physicality; teaching and education. The formed historiographical corpus contains researches focused on all-round reconstruction of personality, creation, ways of thinking, and acts of M. Montaigne. The relevance of the study is ensured by the discovered conceptual multivalence, which indicates the lack of consensus between scientists in the field of M. Montaigne`s personality.